Organizational culture in Serbia in relation to the characteristics of organization - Empirical reserch - Kirin, Snežana; Gavrić, Gordana; Kirin, Sandra (Industrija, 2020)
In moder business conditions, organizational culture is recognized as a powerful tool for long-term survival and development of the organization. The purpose of this paper was to research whether and in what way the characteristics of organizations – such as its size, ownership structure, activity, domestic or foreign – influence the organizational culture. Because of continuous and rapid changes and enormous competition, which are features of modern business, the Denison model of organizational culture was chosen because it emphasizes the need for balance between requirements for organizational stability (factors of mission and consistency) and requirements for its adaptability (factors of involvement and adaptability). The survey covered a sample of 1,000 employees and the data was statistically processed using the one-way ANOVA method. The obtained results show the influence of organizational characteristics on its ability to balance the internal and external focus of the organization, its stability, and its ability to change. Likewise, there should be a certain organizational cultural transformation as a response to the paradigm change in wider environment.